Building Capacity to Evaluate Value Chain Development for Job Creation : A Case Study from Tunisia - Weber, Michael; Salhab, Jade (World Bank, Washington, DC, 2021)
Value Chain Development (VCD) approaches, and building country capacity to adopt them, represent important operational tools to help World Bank client countries harness private sector potential and remove job creation constraints to create more and better jobs, especially for youth, women, and other vulnerable groups. The WBG-coordinated pilot ‘Value Chain Development for Jobs in Lagging Regions, ‘Let’s Work’ Program in Tunisia’ targets pilot value chains that could provide job opportunities for poor or vulnerable groups in lagging regions. The project tests new tools to help inform VCD policies: (a) Cluster and value chain reinforcement initiatives (CRIs), and (b) Value chain and job focused surveys. A ‘VCD Training’, the central capacity building element of the of the Let’s Work program in Tunisia, aimed to build public administration capacity to analyze value chains and support private sector development, job creation, and competitiveness, with a focus on lagging regions. The World Bank designed and delivered the VCD Training in Tunis from April 5, 2016 to November 14, 2016. The eight VCs used for training purposes in the program all link to key WBG financed operations in Tunisia. Two of these value chains, olive oil and medicinal and aromatic plants, were also subjects of subsequent jobs surveys. The VCD Training built strong capacity for VCD analysis in Tunisia. The training helped establish an inter-ministerial ‘Taskforce’ and VCD ‘Platform.’ Overall, 27 civil servants received training, among whom 11 were evaluated as ‘ready to conduct value chain analysis and development work’ by the end of the training program; six of these worked as core members of the Government VCD Taskforce. The VCD capacity development has informed ongoing WBG-financed operations in Tunisia and has been used to train subsequent generations of recruits since the end of the project. All VCs analyzed show high potential for growth, which could lead to more and better jobs in the olive oil, the medicinal and aromatic plants, and tomato sectors.